The long memory effect in ASEAN-6 stock markets from 2006 to 2022: A rescaled range analysis - Almandres, Tricia Q. (Animo Repository, 2023)
This paper aimed to determine whether long memory, persistence, and nonperiodic cycles are present in the ASEAN-6 stock markets from 2006 to 2022. The logarithmic daily returns of each country are divided into three periods: (1) Pre-GFC to GFC, (2) Post-GFC to Pre-COVID, and (3) COVID and U.S. inflationary period. Analysis was conducted through the rescaled range analysis and Hurst exponent, bootstrap, and V-statistics. Results showed that all ASEAN-6 stock markets exhibited long memory effect. Persistence was observed to be the highest during the pre-GFC to GFC, followed by the COVID-19 and U.S. inflationary, and then the post-GFC to pre-COVID. Among the countries, Vietnam had the highest persistence as evidenced by its Hurst coefficients. Thailand, Indonesia, and Malaysia, meanwhile, had the lowest Hurst exponents, making them the best performer for each respective period of interest. Nonperiodic cycles were also detected for the entire time in each stock index. As such, there is a clear evidence of market inefficiencies especially during crisis. Through this methodology, investors and financial institutions can become more aware of the unique investment risks of the ASEAN-6. Particularly, this could help them mitigate some of the risks associated with financial crises. It can also be a reference for regulators in developing policies and regulations to revitalize their economies during financial crises.